Meningkatkan Kepatuhan Wajib Pajak Orang Pribadi melalui Kualitas Pelayanan dan Kesadaran Wajib Pajak - Novi Khoiriawati; Dianita Meirini (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This research aims to prove whether there is an influence on the quality of tax services and taxpayer awareness of the compliance of private taxpayers in Tulungagung Regency. The number of samples used in the study was 245. The data analysis technique used is multiple linear regression. The results showed that there was a positive influence between the quality of tax services on taxpayer compliance. In conclusion, the better the quality of tax services, the higher the compliance of taxpayers. There is a positive influence on taxpayer awareness of taxpayer compliance. This shows that the higher the satisfaction felt by taxpayers, the higher the compliance of taxpayers. Keywords: Compliance, Taxpayer Awareness, Tax Services